A Bibliometric Analysis of Physalis angulata, an Underexplored Agri-Food Resource for Diabetes Management - Sepni Asmira; Auzar Syarif; Fauzan Azima; Kesuma Sayuti (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2026)
Diabetes remains a global challenge, including in Indonesia. Long-term use of commercial drugs has side effects on diabetes patients, therefore exploration and development of natural alternatives must be carried out to minimize the effects of commercial drugs. P. angulata is one of the medicinal plants found in Indonesia that has traditionally been widely used for diabetes treatment, but it has not been widely explored. Although there are a number of studies examining the biological benefits of P. angulata, bibliometric studies are still limited. This study aims to bibliometrically analyze scientific publications from 2000 to 2025 regarding the use of P. angulata in diabetes. We analyzed 288 documents from several publication databases: Scopus, PubMed, and Google Scholar, using VOSviewer. The analysis included publication trends, keyword occurrence, and experimental studies that had been conducted. Publication trends showed an increase, which peaking in 2025 with 32 documents. The Journal of Ethnopharmacology is the top publisher on P. angulata and its association to diabetes. Keyword occurrence reveals that P. angulata is associated with medicinal plants, ethnobotany, phytochemistry, and biological activity, whereas studies on diabetes exist but are confined to in vivo and in vitro investigations, with no clinical trials or food development occurring. A review of experimental studies reveals that P. angulata's bioactive components include antihyperglycemic and antioxidant properties, as well as pancreatic and kidney protective benefits. Recent research has begun to investigate molecular pathways using a molecular docking approach. In conclusion, the findings of this bibliometric analysis suggest that P. angulata has high potential as an agri-food-based bioactive source for diabetes treatment. However, further research is needed, notably in terms of extract standardization, clinical validation in individuals, and the development of future functional food-based formulations followed up by reliable scientific evidence.